Implementasi Direct Costing Method Sebagai Alat Untuk Menghitung harga pokok produksi perusahaan Manufacture (Studi Kasus Industri Flores VCO Nangaba Kabupaten Ende) - Yasintha Gowa; Sabra B. Wahab Thalib; Yulita Londa (ANALISIS, 2020)
Small and Medium Enterprises (SMEs) is a form of community small business and is one of the home industry businesses that has experienced rapid development. Most SMEs still use simple or conventional cost accounting methods in calculating the cost of production while the business world is currently experiencing increasingly rapid development so it must require a current report that is quite accurate and reliable. Direct costing is a method of determining the cost of production that only takes into account variable production costs or which directly affects production volume. Direct costing is often called variable costing and marginal costing. This study aims to determine the implementation of the direct costing method in Nangaba VCO SMEs in addition to knowing the classification of costs in calculating the cost of production using the direct costing method. This type of research is qualitative. Analysis of the data used is a qualitative descriptive analysis which is an analysis that describes or provides an overview of how to determine the cost of goods using variable costing or direct costing in the Nangaba Ende VCO industry. The results of this study indicate that there are differences in the calculation of the cost of production and the net profit made by the company much lower when compared to using the calculation by the direct costing method.